Mordant-free dyeing of nylon fabric with mahogany (Swietenia mahagoni) seed pods: A cleaner approach of synthetic fabric coloration - Mamun, Abdullah Al; Mahbubul Bashar, M; Khan, Sumaiya; Roy, Manindra N; Hossain, Mohammad M; Khan, Mubarak A (Textile research journal, 2022)
The extraction and consequent application of natural colorants obtained from mahogany (Swietenia mahagoni) seed pod powder is described here. The colored solution was extracted by facile boiling in an acidic medium. Fourier-transform infrared spectroscopy indicated that the mahogany seed pod extract contained lignocellulosic substances. The typical strong broad band for -OH stretching vibration appeared at around the 3400 cm−1 region in the spectra indicating the presence of alcoholic groups in the substance. The acidic boiling of the mahogany seed pod extract showed the color bearing character at λmax 400–480 nm in the visible range of the ultra-violet spectrum. Subsequently, commercial single jersey-knitted nylon fabric was dyed with the mahogany seed pod extract. The effects of temperature, pH, and time were investigated meticulously for the above dyeing. The optimum conditions for nylon fabric dyeing with the mahogany seed pod extract were selected as the temperature of 100°C, dyeing time of 60 min, and dyebath pH 4.5. The results were interpreted in terms of color strength and fastness properties. The color fastness to wash and perspiration of nylon fabric dyed with mahogany seed pod extract was found to be moderate to good in the grey scale rating 3–4 to 4 grade in the case of optimum dyeing condition whereas color fastness to light was observed to be poor in the blue wool scale rating 2 grade. It was observed that dyeing time, temperature, and pH had profound influences on the color strength of the dyed material. The color strength was increased with the increase of dyeing period and dyebath temperature. The acidic dye liquor produced the darker hues while the alkaline condition had no effect on color yielding. The fabric was dyed uniformly, confirming the evenness of dyeing which is very important for successful commercial dyeing.